Women and politics - Chowdhury, Najma; Begum, Hamida A.; Islam, Mahmuda; Mahtab, Nazmunnessa; Women for Women (Organization : Bangladesh). (Dhaka Women for Women, 1994)
Collection of papers presented at convention on Women and Politics.
Cover title: Women & politics.
Includes bibliographical references.
Keywords: Feminism -- India; Women -- Political activity -- India; Women -- India -- Social conditions